1976
DOI: 10.1128/iai.14.2.433-438.1976
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the intracellular behavior of Torulopsis glabrata

Abstract: The growth of Torulopsis glabrata was inhibited in glucose-peptone broth containing 10 to 20% normal human serum. Addition of iron to the medium diminshed the fungistatic effect. The intracellular growth of T. glabrata was remarkably restricted within mouse macrophages maintained in vitro, but this growth restriction was not caused by the limitation of iron imposed by the serum in the medium. The intracellular growth of T. glabrata within a very small percentage of the macrophages was not obviously related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In previous works, we and others have addressed the ability of C. glabrata to not only resist the conditions inside the macrophage phagosome, but to even persist and thrive inside [16] [19] . Yet, these investigations have mainly focused on the short-term interaction between host and fungus, lasting for hours up to days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous works, we and others have addressed the ability of C. glabrata to not only resist the conditions inside the macrophage phagosome, but to even persist and thrive inside [16] [19] . Yet, these investigations have mainly focused on the short-term interaction between host and fungus, lasting for hours up to days.…”
Section: Resultsmentioning
confidence: 99%
“…In previous experiments, we observed that C. glabrata microcolonies were regularly found in close proximity to mononuclear cells within murine tissues [15] and speculated that C. glabrata may face constant exposure to these phagocytes during infection. In fact, we and others have shown that C. glabrata can survive and replicate inside macrophages for days in vitro [16] [19] . During commensal growth, fungi are repeatedly exposed, at least transiently, to host-induced stresses (e.g.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Lactate-grown cells were taken up by macrophages less efficiently, but they were more efficient at killing and escaping phagocytosis ( Ene et al, 2013 ). Of note, C. glabrata cells also resist killing by macrophages and have evolved distinct strategies for intracellular survival ( Otto and Howard, 1976 ; Kaur et al, 2007 ; Seider et al, 2010 ). However, in these studies C. glabrata cells were grown in glucose.…”
Section: Introductionmentioning
confidence: 99%
“…3). Owing to its low susceptibility to a number of antimycotics, this organism is of increasing interest as a target f?r new antifungals (9,10). As with Ciclopirox which acts partly by complexing tnetal ions, the efficacy of rilopirox depends on the free metal ion concentration of the growth medium used.…”
Section: Discussionmentioning
confidence: 99%